Cancer alertness as an integral part of residency training in prosthodontic dentistry - O. V. Oreshaka; E. A. Dementieva; A. V. Ganisik; Yu. Yu. Gurevich (Эндодонтия Today)
Despite the emergence of new and improvementof current methods of the diagnostics and treatmentof cancer of the maxillofacial region, its diagnosis is often untimely and late. One of the reasons for this situation is the insufftcientcancer alertness of dentists during the examination of the patient. Therefore, it is very important to emphasize the training of dental residents in this tield, paying particular attention for preventive and sanitary-educational measures and, of course, early diagnosis of precancerous conditions of the maxillofacial region, oral mucosa, tongue and lips. A young specialist should clearly understand the routing of patients with this pathology.